2021
DOI: 10.1186/s12960-021-00574-3
|View full text |Cite
|
Sign up to set email alerts
|

Training in communication skills for self-efficacy of health professionals: a systematic review

Abstract: Background Communication skills are essential for health professionals to establish a positive relationship with their patients, improving their health and quality of life. In this perspective, communication skills training can be effective strategies to improve the care provided by professionals in patient care and the quality of health services. Objective To identify the best available evidence on training programs in communication skills to prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 51 publications
3
52
1
Order By: Relevance
“…Self-efficacy can be improved with training in specific, relevant tasks and challenges. For example, training in communication skills increases self-efficacy for that task, 84 and training in managing interpersonal and coping challenges related to a pandemic increases pandemic selfefficacy. 85 A 2016 meta-analysis of 57 studies involving 22,773 teachers, healthcare workers, and other professionals found an association of medium strength (effect size -0.33) between low self-efficacy and burnout.…”
Section: Self-efficacymentioning
confidence: 99%
“…Self-efficacy can be improved with training in specific, relevant tasks and challenges. For example, training in communication skills increases self-efficacy for that task, 84 and training in managing interpersonal and coping challenges related to a pandemic increases pandemic selfefficacy. 85 A 2016 meta-analysis of 57 studies involving 22,773 teachers, healthcare workers, and other professionals found an association of medium strength (effect size -0.33) between low self-efficacy and burnout.…”
Section: Self-efficacymentioning
confidence: 99%
“…Furthermore, many HCPs perceived more problems in talking about weight and lifestyle in cases when parents had overweight or obesity, and/or when they expected that the child and/or parent would react negatively. This relates to stigmatization of people with obesity that is present among the general public as well as among HCPs (20,21) and asks for education in communication strategies to address this sensitive topic (22), thereby improving HCP's perceived self-e cacy and reducing barriers (2,14,15,23,24). Furthermore, the majority of doctors (GPs, YHCPs and pediatricians) reported that insu cient time is a barrier to talk about weight and lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the majority of doctors (GPs, YHCPs and pediatricians) reported that insu cient time is a barrier to talk about weight and lifestyle. This is a commonly reported barrier in other studies as well, and asks also for health delivery system changes (2,14,15,23,24). Next to education, an improved and sustainable nancial and infrastructural framework is necessary to reduce the obesity stigma, improve obesity care for children, and positively impact HCP's perceived self-e cacy and barriers (6,9,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this research has highlighted three SERVQUAL characteristics, namely reliability, responsiveness, and empathy, that need additional attention and improvement on the part of Malaysian healthcare authorities. Enhancing interpersonal skills training, especially for medical students, ongoing training for health professionals in the workplace, and lean model adaption will substantially enhance the quality of treatment that is currently lacking [79,80]. However, health authorities must realise that the findings are unlikely to be representative of the whole population served by hospitals.…”
Section: Discussionmentioning
confidence: 99%